2020
DOI: 10.35808/ersj/1566
|View full text |Cite
|
Sign up to set email alerts
|

Resources and Competitive Strategies to Improve the Performance of Diving Tourism Business in Indonesia

Abstract: Purpose:This research provides solutions to improve the performance of the diving tourism business in Indonesia by increasing competitive strategies and resource-based uniqueness. Design/Methodology/Approach: The research was conducted using quantitative methods. The unit of analysis is dive operators in Indonesia where data are collected from 50 random samples taken from 284 dive operators. Then the observations in this study use a time horizon that is cross section one shoot taking. Findings: The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Long queues and congestion in tourism areas and the inability to offer more services in tourist areas make many tourists turn to other tourist destinations in neighboring countries such as Malaysia, Singapore, and Thailand (Hengky & Kikvidze 2018). The increasing competition in the tourism industry itself that causes tourists switch their visits to other tourist destinations (Hilmiana et al 2020). The economic crisis experienced by Indonesia due to the pandemic has affected the behavior of tourists to exceed their expectations of tourist destinations (Esquivias et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Long queues and congestion in tourism areas and the inability to offer more services in tourist areas make many tourists turn to other tourist destinations in neighboring countries such as Malaysia, Singapore, and Thailand (Hengky & Kikvidze 2018). The increasing competition in the tourism industry itself that causes tourists switch their visits to other tourist destinations (Hilmiana et al 2020). The economic crisis experienced by Indonesia due to the pandemic has affected the behavior of tourists to exceed their expectations of tourist destinations (Esquivias et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed the impact of both the environment and the company's resources on its result (Charupongsopon and Puriwat, 2017). According to the RBV approach, the performance of an organization is mainly determined by internal resources grouped into three categories, namely: physical resources, human resources and organizational resources (Hilmiana et al, 2020). Therefore, skills and tooling are needed to quickly engage your resources and gain access to those that the company does not have.…”
Section: Introductionmentioning
confidence: 99%